Land Registration Dualism in Indonesia: Normative Legal Analysis and Policy Framework - Novina Sri Indiraharti; Dhany Rahmawan (Yayasan Vifada Cendikia Indonesia, 2026)
Purpose: Indonesia’s land registration system continues to experience structural dualism arising from the coexistence of customary law and national statutory law, resulting in legal uncertainty and recurring land conflicts involving indigenous communities. This study aims to systematically analyse the legal implications of land registration dualism and to formulate a normative legal framework for the recognition of indigenous land rights. Research Design and Methodology: The research employs a normative legal method using statute, case, and historical approaches, within a Critical Legal Studies framework to examine structural legal inequality. The analysis is framed within the Critical Legal Studies perspective, which views law as a product of power relations that may marginalise customary legal systems. Findings and Discussion: The findings indicate that dualism persists due to the absence of clear procedural and institutional mechanisms for recognising and registering customary land within the national system. In response, this study proposes six policy strategies, including formal recognition of indigenous land rights, development of communal certification mechanisms, adoption of legal pluralism, simplification of registration procedures, establishment of a dedicated institution, and integration of customary land data into the national system. Implications: This study offers a normative and structured legal reform model that positions legal pluralism as an operational framework, while also providing practical direction for agrarian law reform through the formal recognition of indigenous land rights, the institutional accommodation of customary land registration, and the strengthening of legal certainty within the national land administration system.